CLIL in minimal input contexts: A longitudinal study of primary school learners' receptive skills. (June 2016) - Pladevall-Ballester, Elisabet; Vallbona, Anna
Abstract: In an attempt to contribute experimental data to the study of CLIL learning outcomes, this paper explores the effect that exposure to CLIL had on the development and achievement of English as a Foreign Language (EFL) receptive skills in a primary school context. Two groups of young learners, one exposed only to EFL sessions and the other one exposed to EFL sessions and an additional CLIL hour per week, were administered a language test at four different times during two academic years. In order to guarantee comparability between the groups, amount of exposure to the target language up to each testing time was kept the same. Results show that in contexts of minimal and equal exposure, CLIL has no remarkable effects, although significant intragroup progress is observed in both contexts. No significant differences are found between the groups with regard to reading skills, and the control group (i.e. EFL-only exposure) significantly outperforms the experimental group (i.e. EFL + CLIL exposure) in their listening skills. Findings seem to suggest that more promising CLIL learning outcomes might only be observable in the long run with more intensive exposure.